1979
DOI: 10.1172/jci109636
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Calcitonin Secretion in Normal Man by Changes of Serum Calcium within the Physiologic Range

Abstract: A B S T R A C T To examine the relative importance of calcium and gastrin in regulation of calcitonin secretion, we administered graded oral doses of calcium to 10 normal men, ages 23-29 yr. Each subject had previously shown an appropriate increase in calcitonin secretion in response to a pharmacologic (0.5 ,ug/kg) pentagastrin injection. On separate days and in random order, each man drank 250 ml of distilled water containing 0.0, 0.5, 1.5, and 3.0 g of elemental calcium as the gluconate salt. Blood samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…iCT was measured with antiserum G-1701 by our previously published method (23). Earlier studies established the capacity of this assay to detect small changes in iCT concentrations (23)(24)(25)(26). We used our "microassay" modification for both assays to permit triplicate determinations with controls for nonspecific binding using only 200 ;J of plasma for each hormone (27).…”
Section: Methodsmentioning
confidence: 99%
“…iCT was measured with antiserum G-1701 by our previously published method (23). Earlier studies established the capacity of this assay to detect small changes in iCT concentrations (23)(24)(25)(26). We used our "microassay" modification for both assays to permit triplicate determinations with controls for nonspecific binding using only 200 ;J of plasma for each hormone (27).…”
Section: Methodsmentioning
confidence: 99%
“…Whether Ca"+ has the same effects in humans, how ionized calcium actually affects serum 1,25(OH)2D3, and whether Ca`+ has a strong regulatory effect when PTH is normal, rather than high, remain unanswered questions. Since transepithelial active transport of calcium by the intestine is regulated by 1,25(0Hh)D3 (39,40), an increase in the hormone augments calcium absorption and can thereby elevate the serum calcium level (41). Therefore, by directly regulating serum 1,25(OH)2D3, calcium appears to control its own absorption.…”
Section: Resultsmentioning
confidence: 99%
“…Patients under anticonvulsant therapy (phenytoin and phénobarbital) were selected for this trial because this association of drugs induces more marked effects on calciotropic hormones [11], PTH values did not change in our patients when compared to controls and showed a negative correlation with CaC values, which was a physio logical condition [ 12], CT did not change either, and, as is the case under physiological conditions, there was a posi tive correlation with CaC [13], As in our case, although with a younger population group, Takesita et al [14] did neither observe PTH nor CT changes. Other authors, such as Weinstein et al [15], found decreased ionic calcium and increased PTH.…”
Section: Discussionmentioning
confidence: 98%